Sluicing e Pseudosluicing em português europeu e brasileiro - Matos, Gabriela; Catarino, Inês (Revista da Associação Portuguesa de Linguística, 2017)
Sluicing and Pseudosluicing are elliptical constructions that differ in Portuguese regarding the (im)possibility of preposition omission. Rodrigues et al. (2009) and Rodrigues (2016) claim that in Brazilian Portuguese (BP), and Spanish, this omission is apparent in Pseudosluicing, because the prepositional phrase occurs inside the elided cleft sentence that affects the overt wh-phrase (whP). European Portuguese (EP) shows that this apparent omission only occurs with whPs that are D-linked and the linguistic context permits the recovering of the nominal that expresses the kind of entities that are under inquire. When free relatives are involved in the cleft sentences, the omission of preposition is required, and the differences in acceptability between PE and PB are due to the narrow extension of the Preposition Drop phenomenon in EP.